Effect of the paste flow rate feeding to an olive decanter on the efficiency of extraction and oil quality - Ibrahim, A. A.; Atta, Nahed M. M.; Mohamed, E. M.; Ahmed, Ana A. A. (2007)
The economic value of olive fruits is focused in its oil content. A practical study on peiralisi olive oil production line at Salhia was carried out to determine the effect of the paste feeding flow rate to the decanter on the extraction efficiency and oil quality. The decanter of theoretical capacity of 2000 kg olive paste hour was used. Different paste feeding flow rates of 2000, 1800, 1600 kg/hr. equal to 100.90 and 80% capacity were used to study the effect of paste feeding flow rate on the efficiency of extraction and oil quality. Four samples from different position (decanter, separators 1 and 2 "oily and water phases" and husk "sansa") during oil separation were collected. Acidity, peroxide value uv, absorbance at 232 and 270 nm. Were determined for olive oil samples to evaluate the oil quality. Total polyphenols, tocopherols content and the stability were determined. Results showed that using flow rate of 80% (1600 kg/hr) gave the highest oil Percent from olive paste and the least residual quantity in pomace. Free fatty acid peroxide value and uv. absorbance at 232 and 270 nm. recorded a slight increased, but total polyphenols, total tocopherols and stability recorded a higher decrease for all samples by increasing the theoretical capacity. These high values of free fatty acid, peroxide value and uv absorbance at 232 and 270nm., and low values of total polyphenols, total tocopherols and stability with increasing the theoretical capacity indicated that low quality of the extraction olive oil. The best quality of olive oil was obtained by using 80% of theoretical capacity. Also the best quality of oil was obtained from horizontal centrifugal decanter compared with that from oily and water phases.
Includes references.
Summary in Arabic.
1
Keywords: Olive oil -- Quality; Olive oil industry; Plant polyphenols